Comparisons of the Health Benefits of Strength Training, Aqua-Fitness, and Aerobic Exercise for the Elderly - Leirós-Rodríguez, Raquel (Rehabil Res Pract, 2018)
OBJECTIVE: To compare strength training, aqua-fitness, and aerobic exercise programs to discern the differences in the benefits achieved by each of the activities in older people. DESIGN: Double-blind randomized trial. SETTING: Controlled clinical environment. PARTICIPANTS: 108 people: 54 female paired with a male of the same age (average age of 65.5 ± 5.6 years). INTERVENTIONS: Three exercise programs (aqua-fitness, aerobic exercise, and strength training) for six months. MAIN OUTCOME MEASURES: Body Mass Index, Senior Fitness Test (which evaluated functional fitness), and the SF-12 Health Survey. RESULTS: Men showed greater positive changes in the aerobic exercise group for general self-perceived mental health, leg strength, and flexibility of legs and arms. The largest improvements in overall self-perceived physical health and upper limb strength were in the men of the strength training group. The women participants in the strength training group obtained greater benefits, especially in self-perceived mental and physical health and in the strength of the four limbs. CONCLUSIONS: To maximise benefits, older people, in general, may want to consider participating in aerobic activity. Furthermore, older women would benefit greatly, both emotionally and physically, from exercise that includes strength training.